2011
DOI: 10.1007/s00703-011-0155-7
|View full text |Cite
|
Sign up to set email alerts
|

Numerical experiments investigating the orographic effects on a heavy rainfall event over the northwestern coast of Taiwan during TAMEX IOP 13

Abstract: An unusual heavy coastal rainfall event ([231 mm day -1 ) occurred during the period of 24-25 June 1987 over the lowland (elevation less than 200 m) and coastal areas in northwest and central Taiwan. The Weather Research and Forecasting (WRF) model is used to investigate the role of synoptic forcing, orographic effects and the diurnal heating cycle on the generation of a prefrontal localized low-level convergence zone offshore leading to the observed coastal rainfall maximum. This case is well simulated by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Thus, the coastline of the Bohai Sea has a complicated form. Previous studies, which explored mechanisms behind the formation and variation of CLLJs, mainly focused on relatively straight coastal area, such as the south and east coast of China (Du et al, ; Lin et al, ) and the west coast of Chile (Q. Jiang et al, ). Their results cannot provide an all‐sided explanation that is suitable for CLLJs occurring in such a complex coastal topography system in Bohai Sea.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the coastline of the Bohai Sea has a complicated form. Previous studies, which explored mechanisms behind the formation and variation of CLLJs, mainly focused on relatively straight coastal area, such as the south and east coast of China (Du et al, ; Lin et al, ) and the west coast of Chile (Q. Jiang et al, ). Their results cannot provide an all‐sided explanation that is suitable for CLLJs occurring in such a complex coastal topography system in Bohai Sea.…”
Section: Introductionmentioning
confidence: 99%
“…BLJs were found over the northwestern Taiwan coast during the early summer rainy season as a result of orographic blocking of the SLLJs by the island terrain (Li and Chen 1998), where they displayed diurnal variation with a maximum in the early morning (Lin et al 2011). The formation of LLJs over the Great Plains (BLJs) is due to inertial oscillations (Blackadar 1957) and shallow baroclinicity produced by the sloping terrain (Holton 1967).…”
Section: Discussionmentioning
confidence: 99%
“…The formation mechanisms could be classified into two types. The first is more related to local diurnal oscillations, such as inertial oscillations (Blackadar 1957; Van de Wiel et al 2010), shallow baroclinicity produced by sloping terrain (Holton 1967) or by land-sea thermal contrast over the coastal regions and orographic blocking (Li and Chen 1998;Lin et al 2011). The second type is more coupled with synoptic or sub-synoptic-scale weather systems, such as isallobaric forcing (Uccellini and Johnson 1979), baroclinicity from the development of extratropical cyclones (Djuric and Damiani 1980;Newton 1967), and diabatic effects (Uccellini et al 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, for all three cases studied, localized heavy rainfall occurs at night as the surface front approaches with increasing strength of the pre-frontal southwesterly monsoon flow. Previous studies have shown that orographic blocking is most pronounced at night and in the early morning when the land surface is coldest (Chen and Li 1995b;Kerns et al 2010;Lin et al 2011).…”
Section: Orographic Effects As the Low-level Trough Approaches Taiwanmentioning
confidence: 99%
“…Convective activity could develop or strengthen over the northwest/west coast of Taiwan (Kerns et al 2010) if offshore convergence is coupled with upper-level divergence under favorable largescale conditions (Chen and Li 1995a;Li et al 1997). Furthermore, the strength of the barrier jet is strongest in the early morning when the land surface is coldest (Chen and Li 1995b;Lin et al 2011).…”
Section: Introductionmentioning
confidence: 99%